Social-Emotional Competence of Inclusive Primary School Teachers in Yogyakarta, Indonesia - Tri Winarsih; Sofia Retnowati; Edilburga Wulan Saptandari (Proceedings of International Conference on Psychological Studies (ICPSYCHE), 2022)
The purpose of this study was to explore the challenges faced by elementary school teachers who accept students with disabilities. The research method used is an exploratory qualitative study, using semi-structured interviews. The participants consisted of 5 primary school teachers and 3 primary school principals both public and private primary schools located in the Special Region of Yogyakarta Province. The results of the study stated that the challenge faced by teachers was that they were not ready to accept students with disabilities. This readiness is seen from the attitude shown by the teacher. Some teachers have a positive attitude and some have a negative attitude towards students with disabilities in their schools. Teachers who have a positive attitude tend to accept students to stay in their schools, and seek appropriate treatment for students. Meanwhile, teachers who have a negative attitude tend to reject students with disabilities, complain about disruptive student behavior in class and are left behind from other students, and feel confused about dealing with students with disabilities. The teacher's attitude towards students with disabilities is part of the teacher's social-emotional competence. Social-emotional competence is needed by teachers in order to be able to handle students with disabilities in their schools. Social- emotional competence will direct teachers to accept students with disabilities, make various efforts so that students with and without disabilities can be handled properly, so that inclusive education can take place effectively.